Combining Ketamine, Brain Stimulation (rTMS) and Mindfulness Therapy (TIMBER) for Opioid Addiction - Pradhan, Basant (Cureus, 2020)
Opioid addiction in the United States currently presents a national crisis despite availability of different treatments. Prior findings suggest that both repetitive transcranial magnetic stimulation (rTMS) and subanesthetic dose of ketamine are efficacious in patients with opioid use disorders (OUD) when administered in isolation. However, their therapeutic value may be undermined by varying clinical responses that tend to dissipate with treatment cessation. There has been no study to date that has used a combination of both for OUD, and there are still many unanswered questions with respect to both. TIMBER (Trauma Interventions using Mindfulness Based Extinction and Reconsolidation of memories) therapy attempts to alter the expression of emotionally charged memories such as traumatic memories, and has been successfully tried in chronic post-traumatic stress disorder (PTSD) and in combination with memory-altering pharmacotherapy like ketamine infusion. By a combination of extinction and reconsolidation of memory approaches, TIMBER works to not over-flood and/or retraumatize as is seen in other treatment approaches. TIMBER involves a balanced combination of both the memory extinction and memory reconsolidation approaches (rather than extinction-only approaches) which explains its superior efficacy in PTSD and benefit in substance use disorders.